(untitled) - FATLAHAH, ANIEK (Jurnal Ilmu Manajemen (JIM), 2013)
Many varieties of ice cream product created to fulfill the customers’s tastes, one of them is chocolate ice cream. Walls Magnum Ice cream is the chocolate ice cream that become the prime product of Walls Ice cream. It’s come with the new formulas, with the segmentation target of adult in the age of 28 to 35 years. The Walls Magnum Ice cream succeded to breaktrough in the list of most likeable ice cream amongs customers. This has been proven by the achievement in rank 3 for Top Brand Image 2012 for Ice cream catagory. The study aims to discuss the impact product quality and brand image on purchase decision ice Walls Magnum Ice Cream inGriya Mapan Santosa Rungkut,Surabaya. Data were analyzed by multiple linier regression. The result showed that the quality product and brand image give contribution of influenced on purchase decision. In this study the dominant effect is a variable quality product. Keywords: product quality, brand image, and purchase decision.